A COMPARATIVE STYLISTIC ANALYSIS OF “THE ETERNAL WANDERER” AND ITS UZBEK ORIGINAL “BOQIY DARBADAR” - Rahmonova Gulhayo Khalilovna (Bright Mind Publishing, 2025)
This article presents a stylistic analysis of Isajon Sulton's “Boqiy darbadar” and its English translation, “The Eternal Wanderer” by Christopher Fort. By comparing the use of various stylistic devices and phraseological units in both languages, the study highlights the challenges and strategies of literary translation. The focus is on key linguistic features such as metaphor, oxymoron, personification, metonymy, irony, and idiomatic expressions. The article examines how these devices are translated, focusing on shifts and adaptations that occur in the process, and how these shifts affect the meaning, tone, and cultural resonance of the text. The study also includes a detailed analysis of translational shifts, including lexical, syntactic, and cultural shifts, offering insights into the complex interplay between the two languages.
Keywords: Stylistic analysis, translation, figurative language, translational shifts, phraseological units, Uzbek literature, literary translation.